2006
DOI: 10.1016/s0140-6736(06)68772-2
|View full text |Cite
|
Sign up to set email alerts
|

Scabies

Abstract: Scabies is a neglected parasitic disease that is a major public health problem in many resource-poor regions. It causes substantial morbidity from secondary infections and post-infective complications such as acute post-streptococcal glomerulonephritis. Disease control requires treatment of the affected individual and all people they have been in contact with, but is often hampered by inappropriate or delayed diagnosis, poor treatment compliance, and improper use of topical compounds such as permethrin, lindan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
341
0
54

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 352 publications
(405 citation statements)
references
References 111 publications
10
341
0
54
Order By: Relevance
“…In a recent seminar in The Lancet [1], we pointed out discrepancies between industrialized and developing countries in the clinical features and epidemiological characteristics of scabies. We concluded that 320 years after the identification of the causative organism, Sarcoptes scabiei, the factors contributing to a high incidence of scabies in vulnerable population groups remain enigmatic.…”
mentioning
confidence: 99%
“…In a recent seminar in The Lancet [1], we pointed out discrepancies between industrialized and developing countries in the clinical features and epidemiological characteristics of scabies. We concluded that 320 years after the identification of the causative organism, Sarcoptes scabiei, the factors contributing to a high incidence of scabies in vulnerable population groups remain enigmatic.…”
mentioning
confidence: 99%
“…The larvae subsequently hatch within 3 days, emerge from the skin, and then burrow again to mature. The host typically mounts an immune response against the mite, which accounts for the pruritus [9,10]. In naive hosts, symptoms can take 2-6 weeks to occur, whereas in non-naive patients, symptoms typically occur within 12-72 h [11].…”
Section: Pathophysiologymentioning
confidence: 99%
“…Scabies typically presents with erythematous papules or nodules with linear burrows in flexural areas, finger and toe web spaces, and in the groin [9] (Fig. 3).…”
Section: Clinical Presentationmentioning
confidence: 99%
“…Crusted scabies are frequently found in immunocompromized patients, such as patients infected with HIV, patients receiving immunosuppressive therapy, individuals with mental retardation, and institutionalized elderly people. Within nursing homes, residents with unrecognized crusted scabies often constitute a source for spread of scabies to other residents and staff members [7].…”
Section: Scabiesmentioning
confidence: 99%